2018
DOI: 10.1097/ta.0000000000001783
|View full text |Cite
|
Sign up to set email alerts
|

Injuries associated with police use of force

Abstract: Epidemiological, level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 15 publications
3
23
0
Order By: Relevance
“…Medical scholarship is an important source of research on injuries related to police use of force, particularly when examining detailed injury data that requires the interpretation of medical records. Collaborations between physicians and criminologists may be particularly fruitful when analysing police generated records and/or when merging police records with medical records (e.g., Bozeman et al., 2017; Strote & Hickman, 2018, 2020). The integration of medical and police records can help discern the nature of injuries attributable to police use of force versus other sources of injury.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical scholarship is an important source of research on injuries related to police use of force, particularly when examining detailed injury data that requires the interpretation of medical records. Collaborations between physicians and criminologists may be particularly fruitful when analysing police generated records and/or when merging police records with medical records (e.g., Bozeman et al., 2017; Strote & Hickman, 2018, 2020). The integration of medical and police records can help discern the nature of injuries attributable to police use of force versus other sources of injury.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a similar vein, Bozeman et al. (2017) looked at all use of force incidents within three mid-sized police departments over a two-year period, and reviewed the severity of injuries across force modalities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fortunately, in both Canada and the US, the application of force [1] is statistically rare, with estimates suggesting that UoF is applied in approximately 0.1% of all police-public interactions (e.g. Bozeman et al , 2018; Hall and Votova, 2013). However, given the vast number of police-public interactions in North America (Baldwin et al , 2018), this low rate translates into a reasonably high number of UoF events in any given year (Shjarback and White, 2016).…”
mentioning
confidence: 99%
“…56 Bozeman et al, 34 found that in 893 use of force incidents in over 1 million calls for service, no significant injuries were reported in 504 applications of the CEW. 35 Bozeman et al, 34 further examined 1,000 CEW exposures of arrestees and found that 99.75 percent did not sustain an injury or had minor injuries. 36 Strote et al, 83 found that of 1,110 uses of CEW significant injuries were rare.…”
Section: While the Identified Symptoms And Combination Of Symptoms Ofmentioning
confidence: 99%
“…[30][31][32][33] Conversely, other studies cited in the literature have not implicated CEWs as a cause of death. [34][35][36][37][38] A syndrome can be described as the association of several clinically recognizable features, signs, symptoms or characteristics that occur together rather than a specific disease. 39 The spectrum of symptoms and behaviors of ExDS overlap with many other disease presentations and there remains no universally recognized diagnostic criteria or consistent definition.…”
Section: Introductionmentioning
confidence: 99%